CHAT GPT Y SU INFLUENCIA EN EL PROCESO DE ENSEÑANZA DE LOS DOCENTES DE LA FACULTAD CIENCIAS JURÍDICAS SOCIALES Y DE LA EDUCACIÓN, PERIODO ACADÉMICO OCTUBRE 2023 – MARZO 2024 - MORAN PUMA MELANY BRITHANY (2024)
This research work delves into the fascinating world of artificial intelligence with a particular focus on the ChatGPT tool and its impact on the teaching process of teachers at the Faculty of Legal, Social and Educational Sciences during the academic period. from October 2023 to March This tool that addresses the potential of technology to transform the educational field as it offers key functions that determine the dynamics in the classroom, the integration of artificial intelligence personified by ChatGPT, is reconfiguring the teaching landscape teacher by opening up new possibilities for personalizing learning, instant feedback, and creating more interactive educational experiences. In this context, research on the use of ChatGPT in teaching becomes an invaluable source of knowledge on how teachers can effectively leverage AI in their pedagogical practices, potentially leading to significant improvements in the quality of education and in the student satisfaction. The fundamental purpose of ChatGPT is to significantly influence the educational process by providing tools for the personalization of learning, encouraging the active participation of students and assisting teachers in the management of large volumes of information. This tool contributes to improving the efficiency the quality of education. Consequently, it is evident that ChatGPT offers a series of advantages for teachers by strengthening the teaching process and student learning. The rapid growth of artificial intelligence, such as ChatGPT, is changing the education sector and enabling new forms of interaction between teachers and students. Research on the use of ChatGPT in education provides insights into its impact on learning